Production of Carbon Quantum Dots Based on Oil Palm Fronds for Polyethylene and Polyethylene Terephthalate Microplastics Detection - Nonni Soraya Sambudi; Maissy Graceline Mulia; Apriliana Cahya Khayrani; Isnaeni; Revathi Raviadaran; Farhana Aziz; Diva Dwira Permana; Randy Suwandi; Kenny Lischer (International Journal of Technology)
Abundant plastic waste degradation to microplastics may cause pollution hazards for the environment. The circulation of microplastic pollution supports the initiation of research related to detecting microplastics in the environment. One method for detecting microplastics is the utilization of the fluorescence properties of carbon quantum dots (CQDs). In this study, CQDs will be produced through the hydrothermal method using oil palm fronds as a carbon source because of their lignin levels of up to 26%. To obtain this carbon, oil palm fronds are crushed and then converted into biochar through a pyrolysis process. Biochar is used as a precursor for the manufacture of CQDs produced through the hydrothermal method at temperature variations of 180°C, 190°C, and 200°C. In this study, CQDs were produced with a peak of 291 nm in the UV wavelength range, which indicates the presence of a ?-?* absorption band in the carbon structure of CQDs. The emergence of dominant C=C, O-H and C=O groups in the FTIR test also proves the success of CQDs production through this hydrothermal method. The CQDs produced at the three temperature variations are less than 10 nm in size and have the highest fluorescence intensity at 200? when excited at 405 nm. Moreover, CQDs exhibit a promising ability for detecting microplastics, as indicated by their decreasing fluorescence intensity trend in response to polyethylene (PE) and polyethylene terephthalate (PET) added solution.